Persistent Jaundice in a Tuberculosis Patient After Treatment: A Rare Case of Primary Sclerosing Cholangitis - Endro Tanoyo; Fahmi Indrarti; Deshinta Putri Mulya; Nur Rahmi Ananda; Naomi Yoshuantari; Bestari Ariningrum Setyawati (MEDICINUS, 2025)
Primary sclerosing cholangitis (PSC) presents diagnostic challenges due to its overlapping features with other conditions. This case report describes a 28-year-old woman with a history of pulmonary tuberculosis who developed jaundice weeks after completing antituberculosis treatment, initially resembling drug-induced liver injury (DILI). In 2021, patient was diagnosed with tuberculous sclerosing cholangitis and showed improvement with antituberculosis therapy. However, in 2022, patient experienced recurrent jaundice, fever, dark urine, and weight loss, without gastrointestinal symptoms. Laboratory tests revealed elevated bilirubin (total 13.8 mg/dl, direct 12.9 mg/dl), increased liver enzymes (SGOT 177 U/l, SGPT 91 U/l), and a positive antinuclear antibody indirect immunofluorescence (ANA IF) test with a centromere pattern. Magnetic resonance cholangiopancreatography (MRCP) and liver biopsy findings supported a diagnosis of PSC, overlapping with tuberculous sclerosing cholangitis. Treatment with ursodeoxycholic acid, methylprednisolone, and mycophenolic acid led to significant improvement in bilirubin and liver enzyme levels, although they remained above the normal range. This case highlights the diagnostic complexity of PSC in tuberculosis patients, particularly in the absence of typical gastrointestinal symptoms. The relationship between tuberculosis and PSC remains unclear, necessitating further investigation. Despite treatment, serum bilirubin and transaminase levels were fluctuated but persisted above the normalrange, highlighting the challenges in managing PSC with concurrent tuberculosis. This report emphasizes the importance of comprehensive diagnostic approaches, including imaging and histopathology, in identifying atypical presentations of PSC.